Primary Sjögren’s Syndrome Adversely Affects the Female Sexual Function Assessed by the Female Sexual Function Index: A Case-Control Study - Çağlar YILDIZ,; Savaş KARAKUŞ,; Özlem BOZOKLU AKKAR,; Ali ŞAHİN,; Birkan BOZKURT,; Ali YANIK, (Archives of Rheumatology, 2017)
Objectives: This study aims to evaluate the sexual function of females with primary Sjögren’s syndrome (pSS) in comparison to healthy females by using the Female Sexual Function Index (FSFI). Patients and methods: This case-control study included 31 female patients (mean age 46.0±10.2 years; range 30 to 68 years) with pSS and 27 healthy females (mean age 44.2±8.5 years; range 30 to 55 years) as control group. The sexual function of the participants was assessed by 19-item FSFI. Results: Mean duration of pSS in the patient group was 35.9 months (range 3 to 264 months). Significantly higher number of pSS patients reported positive history for vaginal infection compared to controls (n=26, 83.9% vs. n=7, 25.9%, respectively; p<0.001) without any difference in endocervical culture result. Cervical smear assessment revealed more inflammation and atrophy in patient group compared to control group (p=0.001). Mean FSFI total score was significantly lower in patient group than control group (18.9±9.9 vs. 25.1±5.1, respectively; p=0.004). Similarly, five out of six domains of FSFI -arousal, lubrication, orgasm, satisfaction, and pain- were significantly lower in patient group. FSFI total and subscale scores, except for pain, were found to be negatively correlated with duration of pSS. Conclusion: The pSS causes sexual dysfunction in female patients. Furthermore, as disease duration increases, female sexual function decreases. Clinical management of female patients with pSS should cover the assessment of their sexual functionality and taking the necessary precautions to maintain satisfactory quality of life and treatment outcome.